Utilization of cardiac MRI for the assessment of suspected rejection with negative biopsy in heart transplant recipients. (25th November 2020) - Anand, S; Young, P; Alnsasra, H; Shrivastava, S; Asleh, R; Murphy, K; Smith, B; Kremers, W; Kushwaha, S; Clavell, A; Steidley, D.E; Pereira, N; et al.
Abstract: Background: Heart transplant (HTx) patients can develop graft dysfunction (GD) without biopsy evidence of cell or antibody mediated rejection. Cardiac MRI (CMR) can detect inflammatory or infiltrative causes of cardiomyopathy however CMR findings in HTx recipients with GD have not been previously described. Purpose: We sought to identify CMR characteristics of HTx patients with GD, and evaluate its additive value in its diagnosis and prognosis. Methods: CMR has been performed routinely to evaluate GD at our institutions. There were 37 HTx recipients who presented with acute decline in left ventricular ejection fraction (LVEF) of <50% and >10% from baseline, with no biopsy evidence of rejection between 2007 and 2018. Coronary angiogram with IVUS was done to rule out allograft vasculopathy. Treatment of GD was per discretion of the treating clinician. Responders were defined as those with LVEF improvement >10% at 180 days or greater post-presentation. LV and RV indices, the presence and pattern of late gadolinium enhancement (LGE) were determined by CMR. Results: There were 34% females and mean age at transplant was 49±13 years. Median time from HTx to GD was 1.2 years. Presenting symptoms were heart failure (n=25), cardiogenic shock (n=1) and 11 patients were asymptomatic. Mean LVEF at presentation was 37±12% and donor specific antibodies were detected in 38% patients. Most patients were treated with steroid bolus (n=29), and/or plasmapheresis (n=23). There were no major changes made in immunosuppression in 6 patients. Delayed enhancement MRI was performed with standard inversion-recovery (IR) gradient echo sequences, between 5 and 20 minutes after institutional-standard protocol administration of IV gadolinium contrast. Biventricular LGE was present in 18/37 (49%) patients with GD and was more prevalent in responders (57%, 13 of 23) than non-responders (35%, 5 of 14), although not statistically significant (p=0.21). There were two patterns of LGE noted: 1) Diffuse epicardial (10 patients out which 9 were responders) and 2) Patchy pattern with non-specific distribution (8 patients out of which 4 were responders). Myocardial edema by triple IR sequencing was seen in 6 patients, all having diffuse epicardial pattern of enhancement matching the delayed enhancement pattern. When comparing different treatment groups, among those treated for GD (n=31), 12 of 21 (57%) responders had LGE and 4 of 10 (40%) non-responders had LGE (p=0.37), a pattern similar to the broader population. Among those not treated for GD (n=6), 1 of 2 responders had LGE and 1 of 4 non-responders had LGE (p=0.5). Conclusion: CMR identified inflammation as a potential cause of GD in approximately 50% of HTx patients. There are 2 distinct patterns of LGE observed in GD, diffuse epicardial (56%) and patchy (44%). Although the presence of LGE in itself is not associated with myocardial recovery, 90% of patients with a diffuse epicardial pattern have recovery of GD. Funding Acknowledgement: Type of funding source: None